Heterotypic and homotypic continuity in psychopathology: a narrative review - Speranza, Anna Maria; Liotti, Marianna; Spoletini, Ilaria; Fortunato, Alexandro (Frontiers in Psychology, 2023)
Psychopathology is a process: it unfolds over time and involves several different factors. To extend our knowledge of such process, it is vital to understand the trajectories that lead to developing and maintaining a specific disorder. The construct of continuity appears very useful to this aim. It refers to the consistency, similarity, and predictability of behaviors or internal states across different developmental phases. This paper aims to present a narrative review of the literature on homotypic and heterotypic continuity of psychopathology across the lifespan. A detailed search of the published literature was conducted using the PsycINFO Record and Medline (PubMed) databases. Articles were included in the review based on the following criteria: (1) publication dates ranging from January 1970 to October 2022; and (2) articles being written in the English language. To ensure a thorough investigation, multiple combinations of keywords such as “continuity,” “psychopathology,” “infancy,” “childhood,” “adolescence,” “adulthood,” “homotypic,” and “heterotypic” were used. Articles were excluded if exclusively focused on epidemiologic data and if not specifically addressing the topic of psychopathology continuity. The literature yielded a total of 36 longitudinal studies and an additional 190 articles, spanning the research published between 1970 and 2022. Studies on continuity focus on the etiology of different forms of mental disorders and may represent a fundamental resource from both a theoretical and clinical perspective. Enhancing our understanding of the different trajectories beneath psychopathology may allow clinicians to implement more effective strategies, focusing both on prevention and intervention. Since literature highlights the importance of early detection of clinical signs of psychopathology, future research should focus more on infancy and pre-scholar age.